A brief account of various treatment modalities for COVID-19 infections - Maduskar, Saumil (International Journal Of Community Medicine And Public Health, 2021)
COVID-19 is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus and has a case fatality rate of 2-3%, with higher rates among elderly patients and patients with comorbidities. It was determined in a study that the viral load peaked during the first week of illness and then gradually declined over the second week. Viral load also correlates with age and the existent of comorbidities. Furthermore, both IgG and IgM antibodies starts to increase by around day 10 after symptomatic onset and most patients had seroconversion within the first 3 weeks. This hints at the fact that the patients are most infectious during the first week of infection and also accounts for the high transmissibility of SARS-CoV-2 during this period